Efficiency of Triple Antibiotic Mixture and Propolis as Intracanal Medication in Revascularization process in immature apex: A clinical study - Mohamed Yehia, Tariq Yehia Abdelrahman; El-Ashry, Salma; El-Batoty, Kareem; El-Hady, Soha (Global Journal of Medical and Clinical Case Reports, 2019)
Introduction: The aim of this clinical study was to evaluate the effect of different antibacterial combinations on the outcome of revascularization process in permanent anterior immature teeth. Methods: Immature necrotic permanent maxillary incisors (n = 40) of patients 8–18 years old were divided into 4 groups according to the intracanal medicament: group 1 was treated with Triple Antibiotic Paste (TAP), group 2 was treated with Ciprofloxacin + Propolis paste (CP), group 3 was treated with Ciprofloxacin + Metronidazole paste (CM), group 4 was treated with Propolis + Metronidazole paste (PM). Cases were followed at regular intervals up to 18 months clinically and radiographically. Results: All cases showed radiographic evidence of periapical healing and continued root development. No statistically significant difference in root length, thickness, apical closure or periapical density between all groups through the whole follow up period. Conclusion: Propolis is successful substitute for ciprofloxacin or metronidazole in DAP for effective disinfection in revascularization process.